Enhancement of optical absorption, photoluminescence and raman transitions in Bi2O3-GeO2 glasses with embedded silver nanoparticles - Martins, Maylon M. [UNESP]; Silva, Diego S. [UNESP]; Kassab, Luciana R. P. [UNESP]; Ribeiro, Sidney J. L. [UNESP]; De Araújo, Cid B. (Sociedade Brasileira de Quimica (SBQ), 2015)
The influence of silver nanoparticles (Ag-NPs) on the optical properties of Bi2O3-GeO2 glasses was investigated aiming the characterization of their potential for applications in photonic devices. The samples were prepared by the melt-quenching technique starting from high purity oxides (GeO2, Bi2O3 and AgNO3). Heat-treatment during different times was performed to nucleate Ag-NPs. A transmission electron microscope was used to confirm the presence of Ag-NPs and to determine their sizes and composition. The glass network was studied by spontaneous Raman scattering. The optical absorption spectra showed an absorption band at ca. 500 nm associated to the bismuth ions, and a 7-fold enhancement of absorption was observed in the samples with Ag-NPs. Photoluminescence (PL) spectra were obtained by exciting the samples with a 808 nm laser. Maximum enhancements of ca. 100% of the PL band centered at 1300 nm and ca. 70% of the Raman spectrum were observed due to the nucleation of the Ag-NPs. The enhanced optical response of the samples with Ag-NPs is attributed to the growth of the local field on the isolated bismuth ions and clusters that are located in the vicinity of the nanoparticles. The results illustrate the large potential of Bi2O3-GeO2 with Ag-NPs to be used in photonic devices.
Keywords: Germanate glass; Heavy metal oxide glass; Infrared photonic device; Silver nanoparticle